Hooded Vulture Necrosyrtes monachus and African White-backed Vulture Gyps africanus nesting at the Olifants River Private Nature Reserve, Limpopo province, South Africa. (20th May 2016) - Monadjem, Ara; Wolter, Kerri; Neser, Walter; Bildstein, Keith
Abstract : Basic ecological information is still lacking for many species of African vultures. The Hooded Vulture Necrosyrtes monachus is known as a rare breeding resident in north-eastern South Africa. This study set out to monitor the nests of Hooded Vultures and, secondarily, White-backed Vultures Gyps africanus in the Olifants River Private Nature Reserve over two breeding seasons in 2013 and 2014. A total of 12 Hooded Vulture nests, placed mostly in the tree Diospyros mespiliformis, were found along the Olifants River, with an average inter- nest distance of 0.76 km. Nest success was estimated to be between 0.44–0.89 offspring pair−1 y−1 in 2013 and 0.50–0.67 offspring pair−1 y−1 in 2014, which are the first estimates for Hooded Vultures in South Africa. It is thought that nests of this species have been under-reported due to the fact that they are placed within or below the canopy of densely leafed trees and hence difficult to view from aerial surveys. African White-backed Vultures also bred along the Olifants River, with nests placed in clusters of up to six. Nesting density of this species ranged from about 1.0 to 1.2 nests km−1 and nests were predominantly placed in Ficus sycomorus trees.